Life-Cycle Labor Supply and Fertility: Causal Inferences from Household Models - Rosenzweig, Mark R.; Wolpin, Kenneth I. (Journal of Political Economy, 1980)
Although estimates of the fertility-labor supply relationship abound, a full appreciation of the interpretation of such estimates has been lacking, regardless of the empirical strategy employed. This paper attempts to elucidate, within the context of a life-cycle decision-making process, the information contained in the estimated association between fertility and labor supply as calculated from "single" and "simultaneous-equations" estimation techniques. We also present a statistical methodology based upon the occurrence of twins in the first pregnancy and provide estimates, using that methodology, of the extent to which women's life-cycle labor supply decisions respond to exogenous (and, in this case, unanticipated) extra children.